Persepsi Guru Terhadap Pembelajaran IPS Terpadu Di SMPN 1 Sei. Beremas Kabupaten Pasaman Barat - Marta, Deddy - (Pendidikan Sejarah, 2014)
Social science (IPS) integrated an integration of various disciplines, such as : sociology, history, geography, econiomics, polotics. Law and culture which aims to establish a democratic human, responsible, sensitive to social problems.The types of the research used in this research is descriptive evaluative study, with qualitative analysis with research sites in SMPN 1Sei . Beremas West Pasaman while the informants in this study is the principal, social science teacher, through the observation, interview and documentation like the form of lesson plans (RPP). The accuracy of the data was cheked by using triangulation of data, the data where analyzed with an interctive modal that consists of data collection, data reduction, data presentation, and conclusion. The result showed that : in general on integrated social science (IPS) in SMPN 1Sei . Beremas be good. In terms of planning the learning process in SMPN 1Sei . Beremas, the teachers have made an annual program, the semester program,syllabus and lesson plans in accordance with its components. In terms of process activities, teaching, social studies teachers at SMPN 1Sei . Beremas is good enough, in accordancewith the teaching profesionalism in carrying out preliminary activities, core activities and activities in accordance with the closing of its components. Based on evaluating the learning, the social science of teacher SMPN 1Sei . Beremas not maximized execute well in reviewing the material , concludes , giving assignments and assessments.Comply with the terms of and execute the taks assigned by principalshows good, the teacher of IPS SMPN 1Sei . Beremas have been able to implement the rules of the regulation as well as the tasks given by principal.The research uf result is the perseption of teachers to learning IPS integreted in SMPN 1Sei . Beremas West Pasaman affect the performance of the integreted social science of teacher so that the teachers performance in accordance with the IPS have their components.